PENDAMPINGAN PERAN KELUARGA DALAM PENDIDIKAN ANAK - Pradnya Permanasari (PENA ABDIMAS : Jurnal Pengabdian Masyarakat, 2020)
The aim of this community service is to change the parents’ mindset in giving the parenting way toward their children especially in education in order that the children can get further education for their future life. I conducted this community service in two ways; by giving counseling to 35 families in the village meeting hall of Kasimpar, Petung Kriyono sub-district, Pekalongan City. I also gave accompaniment system for five families for further process. The result of this activity shows that I managed to change the families’ especially parents’ mindset about the way to educate their children so that they can be motivated to continue their higher education. I also found the parents’ new mindset in educating and supervising their children democratically to keep studying. It can be concluded that all of the samples in this case are parents are able to change their mindsets in how important education is for their children. Key words: families, parenting, children education